Electrochemical treatment of cotton textile-based dyeing effluent. Issue 13 (1st September 2016) - Prajapati, Abhinesh Kumar; Sharma, Neha; Jena, Rakesh Kumar; Shrimal, Preena; Bagtharia, Parth; Kaushal, Rajesh Kumar; Pal, Dharm
ABSTRACT: The electrochemical treatment (ECT) of textile wastewater was carried out in a 1.5 dm 3 electrolyte batch reactor using iron electrodes. With the four plate configurations, a current density (CD) of 89.2 A/m 2 and a pH value of 8.5 were found to be optimal, at which maximum reduction in chemical oxygen demand (COD) and colour achieved were 86% and 79%, respectively. Loss of 0.0666 kg/m 3 iron electrode and 18.44 kWh/m 3 power consumption was observed during ECT with a maximum COD reduction of 79%. The settling characteristics of electrochemically treated effluents as well as the characteristics of foam and residue were also analysed.